The experience economy of the largest walking event in the world: The case of the Nijmeegse Vierdaagse - Thijs Glaap; Polina Ermolaeva (Tourism)
The aim of this research is to investigate the successful factors behind the largest walking event in the world, the Nijmeegse Vierdaagse in the Netherlands, through the prism of a visitors’ experience economy. The study explores the demographic characteristics of the respondents, the visitors’ reasons to attend, as well as an interpretation of their experience. A total of 327 visitors completed a survey expressing their positive recommendation for others to visit the event and the huge interest (99.4%) to re-attend. This was due to a universal level of satisfaction and the diversification of the entertainment provision amongst Dutch, German and other Europeans with a high educational level, aged 20 and above. Most visitors attended the event with their families and friends, for professional and personal training, as part of a military program or for self-development. The main reasons to take part were firstly, to observe the walkers, secondly, to support friends and family and, lastly, for the atmosphere around the city and its history. The experience has been introduced through Pine and Gilmore’s (1998) realms where all four aspects played a huge role in its successful implementation, specifically of the esthetic and entertainment realms. The participants searched mostly for harmony, a pleasant environment and differentiation of cultures. Moreover, the attendees mentioned the educational side as a simplistic curiosity rather than intentional learning, however, they still highlighted that it also mattered as a part of the successful event. Lastly, only small relevance was found in becoming a different person and experiencing a completely different world through escapism. Finally, practically all participants expressed their wish to re-attend the event considering it successful.